The lady in the tower : the fall of Anne Boleyn - Weir, Alison, 1951- (Ballantine Books, 2010)
The tempestuous love affair between Henry VIII and Anne Boleyn scandalized Christendom and altered forever the religious landscape of England. Acclaimed historian and bestselling author Alison Weir draws on myriad sources from the Tudor era to examine, in unprecedented depth, the gripping, dark, and chilling story of Anne Boleyn's final days.